Earliest Detection of Oral Cancer Using Non-Invasive Brush Biopsy Including DNA-Image-Cytometry: Report on Four Cases - Torsten W. Remmerbach; Horst Weidenbach; Alexander Hemprich; Alfred Böcking (Analytical Cellular Pathology)
Objective: We describe four patients presenting early oral cancers, detected cytologically on non‐invasive brush biopsies including DNA‐image cytometry as an adjunctive method before histology on scalpel biopsies confirmed the evidence of malignancy. Methods: Brush biopsies were performed and smears thereof investigated cytologically. After Feulgen restaining, DNA‐measurements were performed using a DNA‐Image‐Cytometer. Case reports: Oral squamous cell carcinomas were diagnosed cytologically in macroscopically suspicious lesions and malignancy confirmed by DNA‐cytometry. The initially performed scalpel biopsies did neither supply evidence of oral cancer nor of severe dysplasia. After at least one to 15 months the occurrence of cancer was finally proven histologically on a second scalpel biopsy each (three microinvasive and one in situ carcinoma). Conclusion: Non‐invasive brush biopsies are a suitable instrument for early cytologic detection of cancer of the mouth. DNA‐image‐cytometry, as an adjunctive method, can be used to confirm the cytologic diagnosis or suspicion of cancer in patients with doubtful lesions (dysplasias). DNA‐aneuploidy is a marker for (prospective) malignancy in smears of the oral cavity, which may detect malignancy months prior to histology. In future this method could be used as a mass screening tool in dentists practise. Colour figures can be viewed on http://www.esacp.org/acp/2003/25‐4/remmerbach.htm.